2021
DOI: 10.1097/meg.0000000000002114
|View full text |Cite
|
Sign up to set email alerts
|

A new panenteric capsule endoscopy-based strategy in patients with melena and a negative upper gastrointestinal endoscopy: a prospective feasibility study

Abstract: Objective patients presenting with melena and nondiagnostic esophagogastroduodenoscopy are usually investigated with colonoscopy and if negative, with small bowel capsule endoscopy. In this pilot study, we tested feasibility and performance of panenteric capsule endoscopy (PCE) in patients presenting with melena and negative esophagogastroduodenoscopy. Methods Between January and December 2018, consecutive patients presenting with melena, clinically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(19 reference statements)
0
16
1
Order By: Relevance
“…Our prospective study compares the performance of SB3 and PillCam Colon 2 capsules for the investigation of suspected small bowel bleeding. Previous studies of pan-intestinal capsule investigation and double headed small bowel capsules have suggested a bidirectional, double headed, capsule, including PillCam Colon 2, designed for colonic imaging, may have a diagnostic advantage in the small bowel (6,7,13,14). Our findings do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Our prospective study compares the performance of SB3 and PillCam Colon 2 capsules for the investigation of suspected small bowel bleeding. Previous studies of pan-intestinal capsule investigation and double headed small bowel capsules have suggested a bidirectional, double headed, capsule, including PillCam Colon 2, designed for colonic imaging, may have a diagnostic advantage in the small bowel (6,7,13,14). Our findings do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 90%
“…A recent systematic review confirmed, pan-intestinal capsule studies with either CCE capsules or specifically designed pan-intestinal capsules (PCE) is a feasible technique, although the majority of studies included were undertaken in an IBD cohort rather than for bleeding (6). More recently, an Italian study confirmed pan-intestinal assessment using CCE (PillCam Colon 2, Medtronic Inc, Dublin, Ireland) was an effective investigation strategy in patients with melena (7). In this study, small bowel bleeding and interventions were undertaken in 50% of cases, suggesting double headed (DH) CCE capsules are a sensitive test for small bowel bleeding.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Gastrointestinal (GI) bleeding is associated with significant healthcare costs [ 1 ]. Even though the presence of melena has conventionally been associated with bleeding proximal to the ligament of Treitz, prompting the use of esophagogastroduodenoscopy as the first diagnostic procedure, this clinical sign has modest localization value [ 2 , 3 ]. Moreover, recent studies have suggested a relative decrease in the incidence of upper GI bleeding [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This becomes particularly relevant when the "timing of the procedure" or "disease extent" are key factors. Indeed, there is growing evidence supporting the use of a panenteroscopic approach in patients with digestive bleeding, in whom an upper digestive tract lesion has been excluded [13,14]. Initial data suggest that in these patients, a timely panenteric evaluation has relevant clinical (increased rate of diagnosis, crucial information for therapeutic work-up) as well as organizational/economic consequences (reduction of the number of unnecessary examinations and hospitalization time).…”
mentioning
confidence: 99%